Non-HPV Perianal and Anorectal Sexually Transmitted Viral Infections - Murphy, Margarita; Chedister, Gabriel Ryan; George, Virgilio (Clinics in Colon and Rectal Surgery, 2019)
This article reviews the epidemiology, diagnosis, and management of common viral infections of the perianal skin and anorectum including herpes simplex virus, human immune deficiency virus, and molluscum contagiosum. Human papilloma virus infection is reviewed in the subsequent article.
Keywords: STDs; HSV; HIV; molluscum contagiosum